A conceptual framework for digital pre-operative planning in Total hip replacement - Azrulhizam, Shapi’i; Anton Satria, Prabuwono, Prof. Madya. Dr.; Riza, Sulaiman, Prof. Madya. Ir. Dr.; Mohammad Khatim, Hasan, Prof. Madya. Dr.; Abdul Yazid, Mohd Kassim, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/